VD_FINDINFO Décision / 2012 / 308 vom 5. Januar 2012 - VD Tribunal cantonal (2012)
ORDONNANCE DE SÉQUESTRE, MOYEN DE PREUVE, CONFISCATIONDROIT PÉNAL | 263 al. 1 let. b CPP (CH), 263 al. 1 let. d CPP (CH), 264 al. 1 let. b CPP (CH)